NEEDS ANALYSIS IN DEVELOPING E-LKPD BASED ON GENIALLY EDUCATIONAL GAMES IN MATHEMATICS LEARNING TO INCREASE LEARNING MOTIVATION - Rohmah, Indah Ainur; Usriyah, Erma Fatmawati Lailatul (ATTA`DIB, 2024)
This study aims to analyze the needs of developing E-LKPD based on Genially educational game in learning mathematics for grade III students at SDIT Ar-Rahmah Yosowilangun. The analysis stages include curriculum, learner, and teacher needs, as well as solution analysis. The research method used is the ADDIE model (Analysis, Design, Development, Implemen-tation, Evaluation) with data collection techniques through observation and interviews. The subjects of this study were third grade students of SDIT Ar-Rahmah Yosowilangun. The re-sults showed that there is a clear need for the development of E-LKPD based on Genially educational game in learning grade III mathematics, due to the low motivation of students to learn. Analysis of curriculum needs indicates the need for innovative approaches to improve the quality of mathematics learning in accordance with the demands of the Merdeka Curricu-lum. The analysis of learners highlights the internal and external factors that influence their interest in mathematics, while the analysis of teachers shows the need for support and facili-tation in developing innovative learning materials. Thus, this study suggests the need for the development of E-LKPD based on the Genially educational game as a solution to increase the learning motivation of grade III students. By utilizing technology and interactive learning approaches, it is expected to create a dynamic and interesting learning environment for stu-dents. In addition, the results of this study can be the basis for developing learning strategies that are more effective and relevant to the needs of students in today's digital era.